A Raman-scattering Study on the Net Orientation of Biomacromolecules in the Outer Epidermal Walls of Mature Wheat Stems (Triticum aestivum) - CAO, YU (Oxford University Press, 2006)
• Background and Aims Raman spectroscopy can be used to examine the orientation of biomacromolecules using relatively thick samples of material, whereas more traditional means of analysing molecular structure require prior isolation of the components, which often destroys morphological features. In this study, Raman spectroscopy was used to examine the outer epidermal cell walls of wheat stems. • Methods Polarized Raman spectra from the epidermal cell walls of wheat stem were obtained using near-infrared–Fourier transform Raman scattering. By comparing spectra taken with Raman light polarized perpendicular or parallel to the longitudinal axis of the cell, the orientation of macromolecules in the cell wall was investigated. • Key Results The net orientation of macromolecules varies in the epidermal cell walls of the different components of wheat stem. The net orientation of cellulose is parallel to the longitudinal axis of the cells, whereas the xylan and the phenylpropane units of lignin tend to lie perpendicular to the longitudinal axis of the cells, i.e. perpendicular to the net orientation of cellulose in the epidermal cell walls. • Conclusions The results imply that cellulose, lignin and xylan form a relatively ordered network that defines the mechanical and structural properties of the cell wall. Such results are likely to have a significant impact on the formulation of definitive models for the static and growing cell wall.